Democratic Discourse in Pakistan: A Critical Examination of Political Parties' Perspectives - Hira Shabbir; Dr. Noreen Saba; Muhammad Ezaan, (Dialogue Social Science Review (DSSR), 2025)
This study examines the different views within different political parties in Pakistan towards democratic trends through a critical discourse analysis (CDA) framework. Utilizing Fairclough's three-dimensional model, this research analyzes political speeches, party manifestos, and social media posts to uncover the linguistic and discursive strategies employed by various parties to construct their understanding of democracy. The findings highlight how parties like (PPP) and (PML-N) emphasize liberal democratic values, whereas parties like (PTI) and Jamaat-e-Islami (JI) advocate for a more Islamic and authoritarian approach. This study demonstrates how political discourse shapes public opinion and legitimates power dynamics in Pakistan's complex political landscape.